Terrorist propaganda: the Red Army Faction and the Provisional IRA, 1968-86 / Joanne Wright. - Wright, Joanne, 1960- (Macmillan, 1991)
Examining the propaganda of two European terrorist groups, the Red Army Faction and the Provisional IRA, this book aims to demonstrate how terrorists exploit and manipulate societies' sensitivities, media channels and government responses.